Consensual hallucination: Bryn Oh's2 Second Life-based work. Issue 1 (1st June 2014) - Toledo Ramírez, Francisco Gerardo
Seductive narrative, magic, 'spells' (in the form of scripts or code), interactive immersion and other affective elements are present and important in Bryn Oh's Second Life-based artwork. In this text, I show that just as it is misleading to exclusively associate the virtual with computers and multimedia technology, it is equally unreliable to assume that the transforming experiences of subjectivity and identity lived in SL are exclusively the result of instrumental technicality of MMORPG's (a virtual multimedia tekhne, so to speak). Virtuality has always been present in literature, poetry, fantasy, daydreaming – all subjective and affective engagements and long-standing artistic resources that produce rapture and immersion. The unfolding narratives, interaction and liminality in Bryn Oh's work capture the visitor's complicity. These are a strategy to embed the visitor into the flow of stories unfolding from Bryn's virtual world, interactive art installations and machinima. A few reflections on Bryn Oh's particular mythopoeia are developed here using three vectors, 3 the hermeneutic value of which explains the arc of interests, aesthetic purposes and locus offered by the artist through her work, intellectual production and media presence in the web, including virtual worlds, SL, blogs, Vimeo and YouTube channels. In connection with these subjects, I apply multidisciplinary views ranging from literature to visual semiotics, media studies to distribute aesthetics. I seek to make sense of these vectors in the form of a 'polyphonic conversation', addressing the particular transformation of Bryn's mythos in affective tekhne. The process reveals important transformations regarding subjectivity and the identity of visiting avatars as well as their 'owners', unfolding through interaction with her artwork. The aim is to contribute to the discussion on virtual worlds, digital and virtual art theories.